Sweet designs : bake it, craft it, style it - Atlas, Amy (Hyperion, 2012)
Amy Atlas, home baker, crafter, and party planner extraordinaire, shows her readers and fans how to create fabulous sweets tables for adults and kids, combining easy recipes, dressed-up store-bought treats, and craft ideas, to make dessert a fitting grand finale to any gathering. More than 100 recipes included.